Unveiling the role of pregnancy associated plasma protein-A in idiopathic preterm labour: a review - Kaundal, Asmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Idiopathic preterm birth (IPTB) is birth before 37 weeks in the absence of any identifiable cause for preterm labour. Prediction and prevention of preterm birth can significantly reduce the burden of morbidity and mortality associated with under-five mortality across the world. Pregnancy-associated plasma protein-A (PAPP-A), a glycoprotein secreted by the placenta, which plays an important role in early placenta development through regulation of the IGF system, has emerged as an excellent biomarker for the prediction of preterm birth. This narrative review aims to understand the possible mechanism by which it is linked to preterm birth and its potential as a predictive biomarker for idiopathic preterm birth.